Sleep in youth with repeated self‐harm and high suicidality: Does sleep predict self‐harm risk?. Issue 6 (24th July 2020) - Asarnow, Joan Rosenbaum; Bai, Sunhye; Babeva, Kalina N.; Adrian, Molly; Berk, Michele S.; Asarnow, Lauren D.; Senturk, Damla; Linehan, Marsha M.; McCauley, Elizabeth
Abstract: Objective: To elucidate processes contributing to continuing self‐harm in youth at very high risk for suicide, focusing on sleep disturbance, a putative warning sign of imminent suicide risk. Method: 101 youth (ages 12–18) selected for high risk of suicide/suicide attempts based on suicidal episodes plus repeated self‐harm (suicide attempts and/or nonsuicidal self‐injury [NSSI]). Youth were assessed at baseline, 6‐, and 12‐month follow‐ups on measures of self‐harm, suicidality, sleep, and depression. Results: Youth showed high rates of baseline sleep disturbance: 81.2% scored in the clinical range on the Pittsburgh Sleep Quality Index (PSQI); 81.2% reported an evening (night owl) circadian preference. PSQI score was associated with elevated levels of self‐harm (suicide attempts and NSSI) contemporaneously and predicted future self‐harm within 30 days. Rates of self‐harm were high during follow‐up: 45.0% and 33.7% at 6 and 12 months, respectively. Conclusions: Results underscore the need to move beyond an acute treatment model to prevent recurrent and potentially deadly self‐harm, the importance of clarifying mechanisms contributing to elevated suicide/self‐harm risk, and the potential promise of engaging sleep as a therapeutic target for optimizing treatment and elucidating mechanistic processes.